Budget of the government of Jigawa State, April-December, 1992 - Jigawa State (Nigeria); Jigawa State (Nigeria). (Dutse : [publisher not identified, 1993)
Approved budget of the government of Jigawa State (Nigeria). published by the Department of Budget & Economic Planning.; Jigawa State (Nigeria). Budget and Economic Planning Directorate.
Title from cover.
usc 11/04/2019
Loans
Keywords: Budget; Expenditures, Public; Jigawa State (Nigeria); Nigeria